2019
DOI: 10.1016/j.jaci.2018.12.1004
|View full text |Cite
|
Sign up to set email alerts
|

Association between rhinovirus species and nasopharyngeal microbiota in infants with severe bronchiolitis

Abstract: Complementing our previous introduction of human neutrophils as APCs in allergic LPR, the results presented here provide insights in their mechanisms of T-cell activation. Our findings indicate that neutrophils fully activate T cells by costimulation of CD2 with CD58 and promote T-cell-mediated inflammation. We conclude that neutrophils, which are recruited in high numbers to inflammatory sites, also contribute to allergic inflammatory diseases through the activation of allergen-specific T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 26 publications
5
25
0
Order By: Relevance
“…Although bronchiolitis has been conventionally considered a single disease entity that has similar mechanisms and clinical characteristics (8), concordant with the current study, recent studies demonstrate important between-virus (respiratory syncytial virus vs. rhinovirus, including different species) differences in the upper airway metabolome (9,13) and microbiome (14,15) profiles. The current study corroborates these prior reports, and extends them by demonstrating between-CoV differences in these molecular characteristics among infants with severe bronchiolitis.…”
Section: Discussionsupporting
confidence: 85%
“…Although bronchiolitis has been conventionally considered a single disease entity that has similar mechanisms and clinical characteristics (8), concordant with the current study, recent studies demonstrate important between-virus (respiratory syncytial virus vs. rhinovirus, including different species) differences in the upper airway metabolome (9,13) and microbiome (14,15) profiles. The current study corroborates these prior reports, and extends them by demonstrating between-CoV differences in these molecular characteristics among infants with severe bronchiolitis.…”
Section: Discussionsupporting
confidence: 85%
“…found that the nasopharyngeal microbiota influenced infection by different rhinovirus species. 51 Infants with a predominant Haemophilus microbiota profile were more likely to have infection by rhinovirus-A species, whereas infants with a predominant Moraxella microbiota profile were more likely to have infection by rhinovirus-C species. 51 Mansbach et al.…”
Section: The Nasal Microbiomementioning
confidence: 94%
“…We analyzed data from the 35th Multicenter Airway Research Collaboration (MARC‐35)—a multicenter prospective cohort study of infants hospitalized with bronchiolitis 6‐13,15,16 . Site investigators enrolled infants (age of <1 year) hospitalized with bronchiolitis at 17 sites across 14 US states (Table ) during three consecutive bronchiolitis seasons (from November through April) in 2011‐2014.…”
Section: Methodsmentioning
confidence: 99%